2015
DOI: 10.18632/oncotarget.3725
|View full text |Cite
|
Sign up to set email alerts
|

Elevated O-GlcNAcylation promotes colonic inflammation and tumorigenesis by modulating NF-κB signaling

Abstract: O-GlcNAcylation is a reversible post-translational modification. O-GlcNAc addition and removal is catalyzed by O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA), respectively. More recent evidence indicates that regulation of O-GlcNAcylation is important for inflammatory diseases and tumorigenesis. In this study, we revealed that O-GlcNAcylation was increased in the colonic tissues of dextran sodium sulfate (DSS)-induced colitis and azoxymethane (AOM)/DSS-induced colitis-associated cancer (CAC) animal models. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 51 publications
4
68
3
1
Order By: Relevance
“…Similar trends have been observed in a number of cancer types including prostate 40; 41; 42; 43 , colon 44; 45; 46; 47; 48 , bladder 49 , hepatocellular carcinoma 50 , leukemia 51; 52 , lung 44; 53 and pancreatic cancer 54 (Table I). Utilizing the Oncomine database, Lynch et al demonstrated that OGT mRNA expression is elevated in prostate cancer tissue compared to normal adjacent tissue in over 200 patients and increased mRNA was associated with a decreased patient five year survival rate 40 .…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…Similar trends have been observed in a number of cancer types including prostate 40; 41; 42; 43 , colon 44; 45; 46; 47; 48 , bladder 49 , hepatocellular carcinoma 50 , leukemia 51; 52 , lung 44; 53 and pancreatic cancer 54 (Table I). Utilizing the Oncomine database, Lynch et al demonstrated that OGT mRNA expression is elevated in prostate cancer tissue compared to normal adjacent tissue in over 200 patients and increased mRNA was associated with a decreased patient five year survival rate 40 .…”
Section: Introductionsupporting
confidence: 80%
“…Additionally, PDAC anchorage-independent growth and survival were dependent on p65 O-GlcNAcylation, as mutation of O-GlcNAc threonine residues resulted in PDAC cell death 54 . In a separate study, elevated O-GlcNAcylation was found to promote colonic inflammation and tumorigenesis via NF-κB 47 . Using a mouse model of induced colitis-associated colorectal cancer, the authors show that elevated O-GlcNAcylation, via heterozygous OGA deletion (+/−), directly leads to colorectal inflammation and tumorigenesis in these mice.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, NButGT also does not disturb insulin signalling in vivo [25]. These complex results were also observed in nuclear factor κB (NF-κB) [26,27] and Wnt signalling [17,28]. The different effects of the changes in O-GlcNAc levels might result from the different methods used to elevate O-GlcNAcylation.…”
Section: Discussionmentioning
confidence: 99%